Severe asthma treated by bronchial thermoplasty: A success not due to the small airways?. Issue 5 (29th January 2019) - Chanez, Pascal; Pahus, Laurie; Charriot, Jeremy; Bourdin, Arnaud
Abstract : See related Article Abstract : See related Article